The imbalance between matrix metalloproteinase 9 and tissue inhibitor of metalloproteinase 1 in acute pancreatitis - Wereszczynska-Siemiatkowska, U.; Siemiatkowski, A.; Swidnicka-Siergiejko, A.; Mroczko, B.; Dabrowski, A. (Zeitschrift für Gastroenterologie, 2015)
Background: The balanced activity of matrix metalloproteinases and their tissue inhibitors is an important, albeit still not completely understood, determinant of extracellular matrix homeostasis, a factor involved in the pathogenesis of acute pancreatitis (AP).Aims: The aim of this study was to compare serum concentrations of matrix metalloproteinase 9 (MMP-9) and its tissue inhibitor (TIMP-1) in patients with AP of various severity and to investigate their relationship with prognostic indicators of AP severity, e. g., polymorphonuclear leukocyte elastase (PMN-E).Patients and Methods: The study included 37 patients with mild (n = 18) or severe AP (n = 19) and 15 healthy controls. Serum concentrations of MMP-9 and TIMP-1 were determined on admission (day 1) and on days 2, 3, 5 and 10.Results: Throughout the study period, the serum MMP-9 concentration in patients with severe AP was significantly higher than those in individuals with mild AP and in healthy controls. In turn, the serum MMP-9 concentrations in persons with mild AP did not differ significantly from those of the controls. The serum TIMP-1 concentrations in both groups were significantly higher than in the controls. Beginning from the 2nd day of hospital stay, the serum TIMP-1 concentration in patients with severe AP was significantly higher than in individuals with mild AP. There were significant correlations between: MMP-9 and PMN-E, TIMP-1 and PMN-E, and MMP-9 and TIMP-1.Conclusion: A disturbed balance between MMP-9 and TIMP-1 observed during the early stages of severe AP suggests that endogenous TIMP-1 is unable to prevent excessive activation and release of MMP-9. MMP-9 may represent a new marker of AP severity.
Keywords: Matrix-Metalloproteinase 9; tissue inhibitors of matrix metalloproteinases, TIMPs; TIMP-1; akute Pankreatitis